If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(w + 4) + -5w = 32 Reorder the terms: 3(4 + w) + -5w = 32 (4 * 3 + w * 3) + -5w = 32 (12 + 3w) + -5w = 32 Combine like terms: 3w + -5w = -2w 12 + -2w = 32 Solving 12 + -2w = 32 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -2w = 32 + -12 Combine like terms: 12 + -12 = 0 0 + -2w = 32 + -12 -2w = 32 + -12 Combine like terms: 32 + -12 = 20 -2w = 20 Divide each side by '-2'. w = -10 Simplifying w = -10
| 30-2x=12+4x | | 3(x-1)+4=25 | | (8x-9)-(7x-9)= | | 5(5p-5)+7p=167 | | C=0.10x+7 | | 56m^2+376m+240=0 | | 6x+30=4x-6 | | 6x=d+2 | | 1=7-4/5x/5x | | x/(0.3-x)=5 | | 9(x+5)=36 | | 1/5d=7-4/x | | 56=4x-4(-x-4) | | radius=8in | | 4/3pi5^3 | | 3(2x+3)=5(2-x) | | X^2-8x-24x+64=0 | | xln(4-x^2)=0 | | 4x-9=18-5x | | (2a^5b)^2/24b^6 | | Tanx+2=1.9 | | 7s+4q-5s+3q= | | a(19)=12-2n | | X^2-12x+84=12y | | 2r-4=5(r+7) | | y=3x^2-36x-100 | | 8(6+7)+x=7x | | 2(27-b)=100-4b+6(s-b) | | 5x-13=4x-2 | | 5x-13=4x-2•/.2 | | 2/3(2-x)-1/2(2x+5)=5/6(-x-3) | | Y^10/Y^6 |